Geopolitics Codes di Asia Tenggara dalam Geopolitical Structures Indo-Pasifik - Sulistyo, Iwan; Karisma, Gita (Andalas Journal of International Studies (AJIS), 2021)
By using three main concepts, namely geopolitical agents, geopolitical structures, and geopolitical codes, this study examines how the geopolitics of Southeast Asia after the Indo-Pacific initiative in 2007, especially in the framework of the ASEAN Outlook on Indo-Pacific. Assessing qualitatively-descriptively through analyzing data from various books, journals and credible websites, the authors argue that, apart from ASEAN, there are also a number of actors/agents in the form of countries that have influence in the geopolitical structure, especially in Southeast Asia and even in the Indo-Pacific in general, namely Singapore, Indonesia, the Philippines, Thailand and Malaysia. The concepts of The Free and Open Indo-Pacific (FOIP) and the ASEAN Outlook on Indo-Pacific (AOIPs) have also been part of the Indo-Pacific geopolitical structures. While the Philippines and Singapore tend to take sides in supporting the US Indo-Pacific idea, some of the other actors, namely Thailand, Malaysia, Myanmar, Laos, Cambodia, actually show a neutral position.